INSERTING READ, ENCODE, ANNOTATE AND PONDER (REAP) STRATEGY TO ENHANCE STUDENTS’ READING COMPREHENSION - Hasriani Hasriani; Nur Aeni; Andi Suwarni (Universitas Negeri Makassar, 2023)
The purpose of this study is to determine whether or not utilizing the REAP technique can help students with reading comprehension, specifically at the literal and inferential levels. By administering multiple choice reading questions as an instrument for the pre-test, treatment, and post-test with one group, the researcher employed a pre-experimental approach to gather data regarding narrative texts. The class IX.9 students from SMP Negeri 9 Makassar served as the study's sample. The results of this study showed that there was an improvement in score following treatment. Based on the paired sample test, where the sig (2-tailed) value is 0.00 0.05, it can be concluded that the use of read, encode, and annotate was successful.